2020
DOI: 10.1111/jcmm.15358
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibitor protects chronic cerebral hypoperfusion and oxygen‐glucose deprivation injuries via H3K14 and H4K5 acetylation‐mediated BDNF expression

Abstract: Vascular dementia (VaD) is the second most common cause of dementia, but the treatment is still lacking. Although many studies have reported that histone deacetylase inhibitors (HDACis) confer protective effects against ischemic and hypoxic injuries, their role in VaD is still uncertain. Previous studies shown, one HDACi protected against cognitive decline in animals with chronic cerebral hypoperfusion (CCH). However, the underlying mechanisms remain elusive. In this study, we tested several 10,11‐dihydro‐5H‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Previous studies have shown the protective effects of HDACi on vascular cognitive impairment induced by CCH via histone acetylation 1 and in OGD conditions via differential BDNF isoform expression 5 . We subsequently investigated which spatial regions of the protein levels of BDNF would be affected by HDACi under CCH injury.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have shown the protective effects of HDACi on vascular cognitive impairment induced by CCH via histone acetylation 1 and in OGD conditions via differential BDNF isoform expression 5 . We subsequently investigated which spatial regions of the protein levels of BDNF would be affected by HDACi under CCH injury.…”
Section: Resultsmentioning
confidence: 97%
“…One HDACi in particular, compound 13, increases the acetylation status in histones 3 and 4, which further react with specific promotors of BDNF 5 . BDNF acted as a modulator to induce changes in gene expression or protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations